Analysis of the quality measurement of the lppm Bina Bangsa university e-journal website using the webqual 4.0 method - Ruchmaryeni, Ruchmaryeni; Rahmadani, Kurniati; Irfan, Mursyid (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the quality of digital-based e-journals using the WebQual 4.0 model, which consists of three main variables: usability, information quality, and service interaction quality. Usability variables include ease of navigation, interface display, and user experience in accessing e-journal features. Information quality assesses the completeness, accuracy, relevance, and clarity of the content presented, while service interaction quality focuses on system reliability, transaction security, and the responsiveness of digital services to user needs. The research method uses a quantitative approach by distributing questionnaires to e-journal users and analyzing them using inferential statistical techniques to measure the influence of each variable on user satisfaction levels. The results show that the three WebQual 4.0 variables contribute significantly to improving the quality of e-journals, with information quality as the dominant factor. The scientific contribution of this study lies in strengthening the theoretical framework in evaluating the quality of digital e-journal platforms, so that it can serve as a reference in developing web-based service quality assessment models in the academic and scientific publication realms, not only providing practical implications but also enriching the academic literature related to the quality of digital information systems.